Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1108/10569211111165316
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice, age, and performance connection in Malaysia

Abstract: Purpose -The paper aims to examine the links between organizational justice (distributive justice and procedural justice) and job performance (task performance and contextual performance). The moderating role of age in the above-mentioned relationship was also investigated. Design/methodology/approach -Data were gathered using self-administered questionnaires from a sample of 136 customer-contact employees within the telecommunications industry of Malaysia. Findings -The results demonstrated that distributive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
0
18
1
2
Order By: Relevance
“…Research in social psychology indicates that younger and older employees have different expectations regarding work and this may impact on their work performance. Older employees are likely to focus on procedural justice, as they focus on feelings of personal importance, and younger employees emphasise distributive justice owing to their need for economic security and success (Nasurdin & Khuan, 2011). The results of the analysis of variance for respondents from the different departments and setting criteria showed that the Customer Service Department was most satisfied with the construct of setting criteria, scoring a mean average of 6.03.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Research in social psychology indicates that younger and older employees have different expectations regarding work and this may impact on their work performance. Older employees are likely to focus on procedural justice, as they focus on feelings of personal importance, and younger employees emphasise distributive justice owing to their need for economic security and success (Nasurdin & Khuan, 2011). The results of the analysis of variance for respondents from the different departments and setting criteria showed that the Customer Service Department was most satisfied with the construct of setting criteria, scoring a mean average of 6.03.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…These are the following principles (Bias & Moag, 1986): creates the felling of the employees that they are valuated and that they are an important part of the organization (Kalay, 2016). These positive feelings could encourage employees to reciprocate behaviour or even to demonstrate behaviour that go beyond their formal role (Nasurdin & Khuan, 2011). This, furthermore, can positively affect the performance achieved by individuals as well as the overall organizational performance.…”
Section: The Review Of Literature On Organizational Justice and Develmentioning
confidence: 99%
“…Employee performance has been under discussion and evaluation as one of the most important variable in psychology and business research (Borman, 2004a;Borman andMotowidlo, 1993, 1997;Organ, 1997;Johari and Yahya, 2016). Employee performance is a key predictor of organizational performance hence, examined from many different dimensions (Organ, 1997;Emmerik & Sanders, 2004;Nasurdin & Khuan, 2011;Saputra et al, 2015). Motowidlo (2003) argued that employee performance can be assessed in terms of task-related aspects, expected behaviors, and most importantly financial figures.…”
Section: Employee Performancementioning
confidence: 99%
“…Task output deals with how much quality work is done, whereas job-related behavior is considered as the behavioral side that is beneficial in attaining task accomplishment/performance. Employee performance can be judged through the formal behavior while producing goods and services those appear on employee's job description (Nasurdin and Khuan, 2011;Saputra et al, 2015).…”
Section: Employee Performancementioning
confidence: 99%